2010
DOI: 10.1016/j.neuroscience.2010.09.051
|View full text |Cite
|
Sign up to set email alerts
|

An adenylyl cyclase signaling pathway predicts direct dopaminergic input to vestibular hair cells

Abstract: Adenylyl cyclase signaling pathways have been identified in a model hair cell preparation from the trout saccule, for which the hair cell is the only intact cell type. The use of degenerate primers targeting cDNA sequence conserved across adenylyl cyclase (AC) isoforms, and RT-PCR, coupled with cloning of amplification products, indicated expression of AC9, AC7 and AC5/6, with cloning efficiencies of 11:5:2. AC9 and AC5/6 are inhibited by Ca2+, the former in conjunction with calcineurin, and message for calcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 62 publications
1
33
1
1
Order By: Relevance
“…Our data show that cGMP is a potent modulator of I h , and in vivo cGMP levels could be modulated through nitric oxide activation of guanylyl cyclase (Garthwaite 2008). Dopamine is found in auditory efferents (Gáborján et al 1999), and immunoreactivity for dopamine receptor subtypes D1A and D2L was reported on both inner and outer faces of calyces from the rat saccule and mouse utricle (Drescher et al 2010). It is tempting to speculate that elevating levels of intracellular cyclic nucleotides could enhance firing in calyx afferents through I h ; however, further experiments are required to provide a possible direct link between I h modulation and efferent input to the calyx.…”
Section: Is I H Modulated By Efferent Neurotransmitters?mentioning
confidence: 63%
See 1 more Smart Citation
“…Our data show that cGMP is a potent modulator of I h , and in vivo cGMP levels could be modulated through nitric oxide activation of guanylyl cyclase (Garthwaite 2008). Dopamine is found in auditory efferents (Gáborján et al 1999), and immunoreactivity for dopamine receptor subtypes D1A and D2L was reported on both inner and outer faces of calyces from the rat saccule and mouse utricle (Drescher et al 2010). It is tempting to speculate that elevating levels of intracellular cyclic nucleotides could enhance firing in calyx afferents through I h ; however, further experiments are required to provide a possible direct link between I h modulation and efferent input to the calyx.…”
Section: Is I H Modulated By Efferent Neurotransmitters?mentioning
confidence: 63%
“…Electrical stimulation of the efferent system leads to an increase in firing in mammalian vestibular afferents and calyx units show the largest responses to efferent stimulation (reviewed in Holt et al 2011). ACh is thought to be a major efferent neurotransmitter, but other candidate transmitter molecules include ATP, calcitonin gene-related peptide, opioid peptides, γ-aminobutyric acid, nitric oxide, and dopamine (Drescher et al 2010;Holt et al 2011). Efferent transmitters could potentially influence I h gating by modulating intracellular levels of cyclic nucleotides.…”
Section: Is I H Modulated By Efferent Neurotransmitters?mentioning
confidence: 99%
“…In contrast, DA increases the excitability of hair cells in the zebrafish lateral line through a D1‐like receptor mechanism (Toro et al, ). Isolated hair cells from rainbow trout express both D1‐like and D2‐like receptor mRNA (Drescher et al, ), as do homogenates of larval zebrafish utricular and saccular maculae (Toro et al, ). To our knowledge, there is no evidence for a direct DA modulation of cholinergic efferents in the peripheral auditory system, but dopaminergic and cholinergic systems have well characterized interactions in the central nervous system (Acquas & Chiara, ; Moore, Fadel, Sarter, & Bruno, ).…”
Section: Discussionmentioning
confidence: 99%
“…This antibody recognizes ã 60kDa band from mouse brain lysate on Western blot (manufacturer's data) and labels known catecholaminergic neuronal populations in rodent brain (e.g., Kaufling et al, 2009). Importantly, in midshipman, AB1542 shows the same pattern of labeling on adjacent sections in the saccule as the monoclonal anti-TH (MAB318, above) and a similar pattern of innervation in mammalian saccule (Drescher et al, 2010) and cochlear sensory epithelium (Darrow et al, 2006a;Niu and Canlon, 2006; see Discussion) as other polyclonal TH antibodies. Adjacent sections from positively labeled sections incubated without primary or secondary antisera showed a complete absence of labeling.…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…Furthermore, dopamine receptor mRNA expression was recently found in hair cell preparations of the trout saccule (Drescher et al, 2010). Thus, there is compelling evidence that dopamine action on the inner ear may be a common feature across unrelated species of teleost fishes, and perhaps vertebrates in general.…”
Section: Th-ir Neurons In the Periventricular Posterior Tuberculum Hamentioning
confidence: 99%